Continuous Femoral Nerve Block Provides Superior Analgesia Compared With Continuous Intra-articular and Wound Infusion After Anterior Cruciate Ligament Reconstruction. Issue 2 (1st February 2009) - Dauri, Mario; Fabbi, Eleonora; Mariani, Pierpaolo; Faria, Skerdilajd; Carpenedo, Roberta; Sidiropoulou, Tatiana; Coniglione, Filadelfo; Silvi, Maria B.; Sabato, Alessandro F.
Abstract : Background and Objectives: This prospective, randomized, clinical trial compared pain intensity and analgesic drug consumption after anterior cruciate ligament (ACL) reconstruction with patellar tendon under femoral-sciatic nerve block anesthesia in patients who received either a continuous femoral nerve block (CFNB) or continuous local anesthetic wound and intra-articular infusions. Methods: Fifty patients were randomized to CFNB (n = 25) or an ON-Q device (I-Flow Corp, Lake Forest, Calif) (n = 25). All patients received sciatic nerve block (25 mL of ropivacaine 7.5 mg/mL and clonidine 30 μg). The first group received a CFNB (2 mg/mL of ropivacaine at 7 mL/hr), and the second group received a single-shot femoral nerve block (both using 25 mL of ropivacaine 7.5 mg/mL and clonidine 30 μg). At the end of the intervention, an ON-Q device was positioned on the ON-Q patients to continuously infuse the patellar tendon wound and intra-articular cavity with ropivacaine 2 mg/mL at 2 mL/hr for each catheter. Data regarding demographic, hemodynamic, pain scores, adverse effects, and need for supplemental analgesia were registered in a 36-hr follow-up period. Results: The CFNB group reported lower visual analog scale values than the ON-Q group: at rest at 12 hrs (2.4 [SD, 2.2] vs 5.4 [SD, 3.1]; P < 0.001) and on movement at 12 (3.1 [SD, 2.5] vs 6.3 [SD, 2.9]; P < 0.001) and 24 hrs (2.7 [SD, 1.9] vs 4.6 [SD, 2.6]; P = 0.01) after surgery. The number of morphine and ketorolac boluses was lower in the CNFB group (morphine: 3.2 [SD, 2.2] vs 6.2 [SD, 2.5]; P < 0.001; ketorolac: 1.1 [SD, 1.0] vs 2.4 [SD, 0.9]; P < 0.001). Conclusion: Continuous femoral nerve block provides better analgesia than the continuous patellar tendon wound and intra-articular infusions after anterior cruciate ligament reconstruction with patellar tendon.